Soft-bit decoding of regular low-density parity-check codes - Howard, S.L.; Gaudet, V.C.; Schlegel, C. (IEEE transactions on circuits and systems. II, Express briefs, 2005)
A novel representation, using soft-bit messages, of the belief propagation (BP) decoding algorithm for low-density parity-check codes is derived as an alternative to the log-likelihood-ratio (LLR)-based BP and min-sum decoding algorithms. A simple approximation is also presented. Simulation results demonstrate the functionality of the soft-bit decoding algorithm. Floating-point soft-bit and LLR BP decoding show equivalent performance; the approximation incurs 0.5-dB loss, comparable to min-sum performance loss over BP. Fixed-point results show similar performance to LLR BP decoding; the approximation converges to floating-point results with one less bit of precision.